Momentum Transfer in Hypervelocity Impact Experiments on Rock Targets. (2015) - Hoerth, Tobias; Schäfer, Frank; Hupfer, Jan; Millon, Oliver; Wickert, Matthias
Abstract: A special phenomenon observed in hypervelocity impacts on rock targets is the so-called momentum multiplication, i.e. the momentum transferred to the target is greater than the original momentum of the projectile. This effect is caused by ejection of debris in the direction opposite to the flight direction of the projectile. In the present study momentum multiplication was investigated as a function of target material properties and projectile velocity. Hypervelocity impact experiments on target materials with different porosities were conducted and the momentum transfer was measured using a ballistic pendulum. Low porous materials like quartzite show larger momentum multiplication than porous materials like sandstone. The smallest momentum multiplication was measured for highly porous aerated concrete. Higher projectile velocity leads to higher momentum multiplication. Furthermore, this increase is stronger for low porous materials compared with porous materials. These observations can be explained by the different ejection behavior. Low porous materials show a directional and very fast ejection whereas porous materials show a slower ejection. The highly porous material shows a diffuse ejection behavior. Furthermore, cratering efficiency is reduced in porous targets leading to a smaller amount of ejected debris. This effect is attributed to energy dissipation caused by irreversible crushing of pore space.